2019
DOI: 10.4103/meajo.meajo_194_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of dry eye disease among 40 years and older population of Riyadh (Except Capital), Saudi Arabia

Abstract: PURPOSE: The prevalence and determinants of dry eye disease (DED) among 40 years and older population of Riyadh (except capital), Saudi Arabia. SUBJECTS AND METHODS: A population-based survey was conducted in Riyadh district between 2013 and 2017. All Saudi aged >40 years attended at the Primary Health Center were the study population. McCarty Symptom Questionnaire was adopted. A representative sample was examined. The best-corrected visual acuity and anterior and poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 25 publications
2
35
1
1
Order By: Relevance
“…The latest development is a prevalence study of DE in Riyadh district based on a prospective study by utilising the McMonnies' DE questionnaire. 12 A similar study reported that the overall prevalence of DE was 35.9% in cases ≥ 40 years of age (Table 1). Another study, which observed the frequency of DE in the Northern Region of Saudi Arabia, was performed by Alsweilem et al 19 Their sample consisted of 384 teenagers, which was investigated at 3 months for data collection.…”
Section: Prevalence Of Dry Eyementioning
confidence: 69%
See 3 more Smart Citations
“…The latest development is a prevalence study of DE in Riyadh district based on a prospective study by utilising the McMonnies' DE questionnaire. 12 A similar study reported that the overall prevalence of DE was 35.9% in cases ≥ 40 years of age (Table 1). Another study, which observed the frequency of DE in the Northern Region of Saudi Arabia, was performed by Alsweilem et al 19 Their sample consisted of 384 teenagers, which was investigated at 3 months for data collection.…”
Section: Prevalence Of Dry Eyementioning
confidence: 69%
“…This may be because of the high percentage of rheumatoid arthritis, DM and the use of age-related systemic and topical medications, which may lead to deterioration of TF intact. 5,12 Furthermore, gender is another factor that has been documented to influence TF profile. 6,7 Arab data found altered rate of tear production in women as compared to men, particularly after…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lower medication burden may facilitate a more optimal adherence to medication. 6,[24][25][26] Moreover, dry eye is highly prevalent amongst the Saudi population 27,28 and the use of antiglaucoma medication can cause further damage to the ocular surface. A reduction of topical anti-glaucoma medications after ab interno trabecular bypass surgery may improve the ocular surface.…”
Section: Discussionmentioning
confidence: 99%